2000
DOI: 10.4049/jimmunol.165.1.442
|View full text |Cite
|
Sign up to set email alerts
|

The LFA-1 Integrin Supports Rolling Adhesions on ICAM-1 Under Physiological Shear Flow in a Permissive Cellular Environment

Abstract: The LFA-1 integrin is crucial for the firm adhesion of circulating leukocytes to ICAM-1-expressing endothelial cells. In the present study, we demonstrate that LFA-1 can arrest unstimulated PBL subsets and lymphoblastoid Jurkat cells on immobilized ICAM-1 under subphysiological shear flow and mediate firm adhesion to ICAM-1 after short static contact. However, LFA-1 expressed in K562 cells failed to support firm adhesion to ICAM-1 but instead mediated K562 cell rolling on the endothelial ligand under physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 65 publications
7
98
1
4
Order By: Relevance
“…Substrates were subsequently overlaid with various concentrations of ICAM-1-Fc. Ligand densities were assessed as previously described (25). Isolated T cells were washed in 5 mM EDTA containing medium and were suspended in H/H medium (HBSS containing 2 mg/ml BSA and 10 mM HEPES, pH 7.4) in the presence of the indicated peptides or reagents.…”
Section: In Vitro Shear Flow Assaysmentioning
confidence: 99%
“…Substrates were subsequently overlaid with various concentrations of ICAM-1-Fc. Ligand densities were assessed as previously described (25). Isolated T cells were washed in 5 mM EDTA containing medium and were suspended in H/H medium (HBSS containing 2 mg/ml BSA and 10 mM HEPES, pH 7.4) in the presence of the indicated peptides or reagents.…”
Section: In Vitro Shear Flow Assaysmentioning
confidence: 99%
“…Site densities of coated sVCAM-1 were determined as described (25,27). The polystyrene plates were each assembled on the lower wall of the flow chamber (260-m gap) (28).…”
Section: Vcam-1 Microbead Bindingmentioning
confidence: 99%
“…However, the ability of VLA-4 to tether cells and support their rolling on the endothelial ligand, VCAM-1, 1 under shear flow does not require high affinity to soluble ligands (9). In addition, previous studies suggested that VLA-4 and LFA-1 associations with the intracellular actincytoskeleton control integrin adhesiveness to ligand under shear flow and are independent of the intrinsic affinity of these integrins to their respective ligands (5,6). Accordingly, the ability of leukocyte integrins to self-cluster upon ligand binding has been predicted to facilitate the generation of high avidity tethers under disruptive shear forces even without acquisition of conformations with high affinity to monovalent ligands (10).…”
mentioning
confidence: 97%
“…The firm adhesions are mediated exclusively by subsets of leukocyte integrins, which include ␣ 4 ␤ 7 , VLA-4 (␣ 4 ␤ 1 ), and LFA-1 (3,4). These integrins exhibit basal recognition of ligand under shear flow and enable leukocyte capture, rolling, and arrest on their respective endothelial ligands when present at sufficiently high densities (5,6). This basal integrin adhesiveness can be dramatically augmented by leukocyte exposure to appropriate endothelial chemokines in situ, which enhance integrin avidity through their respective G-protein-coupled receptors on tethered leukocytes (7,8).…”
mentioning
confidence: 99%